Vaccine confidence, public understanding and probity: time for a shift in focus?. Issue 4 (9th March 2021) - Wheelock, Ana; Ives, Jonathan
Abstract : Lack of vaccine confidence can contribute to drops in vaccination coverage and subsequent outbreaks of diseases like measles and polio. Low trust in vaccines is attributed to a combination of factors, including lack of understanding, vaccine scares, flawed policies, social media and mistrust of vaccine manufacturers, scientists and decision-makers. The COVID-19 crisis has laid bare societies' vulnerability to new pathogens and the critical role of vaccines (and their acceptability) in containing this and future pandemics. It has also put science at the forefront of the response, with several governments relying on academics to help shape policy and communicate with the public. Against this backdrop, protecting public trust in scientists and scientific output is arguably more important than ever. Yet, conflicts of interest (CoI) in biomedical research remain ubiquitous and harmful, and measures to curb them have had limited success. There is also evidence of bias in industry-sponsored vaccine studies and academics are voicing concerns about the risks of working in a CoI prevalent research area. Here, we set out to challenge established thinking with regard to vaccine confidence, by shifting the gaze from a deficit in public understanding towards probity in research relationships and suggesting an alternative and perhaps complementary strategy for addressing vaccine mistrust. We argue that a concerted effort needs to be made to revisit the norms that undergird contemporary vaccine research, coupled with a willingness of all stakeholders to reimagine those relationships with an emphasis on demonstrating trustworthiness and probity.